The art of gender training - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Gender training in Ghana. Politics, issues and tools Edited by D Tsikata, Woeli Publishing Services, Ghana, 2001. 450 pp. ISBN 9964978766 GBP 21.50 Euro 34.55